2017
DOI: 10.1523/jneurosci.2851-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Synaptic Amyloid-β Generation through BACE1 Retrograde Transport in a Mouse Model of Alzheimer's Disease

Abstract: Amyloid-␤ (A␤) peptides play a key role in synaptic damage and memory deficits in the early pathogenesis of Alzheimer's disease (AD).Abnormal accumulation of A␤ at nerve terminals leads to synaptic pathology and ultimately to neurodegeneration. ␤-site amyloid precursor protein (APP) cleaving enzyme 1 (BACE1) is the major neuronal ␤-secretase for A␤ generation. However, the mechanisms regulating BACE1 distribution in axons and ␤ cleavage of APP at synapses remain largely unknown. Here, we reveal that dynein-Sna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
64
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 81 publications
6
64
0
Order By: Relevance
“…Ye and Cai (2014) recently reported that BACE1 accumulates in late endosomes that cluster at presynaptic terminals of hippocampal neurons in the human APP (hAPP) transgenic mouse model of AD, which produces amyloid pathology in mice comparable to human AD, and in AD patient brains. Given that the lumen of late endosomes is acidic, which is necessary for optimal BACE1 activity (Das et al, 2013), this finding is consistent with the hypothesis that A␤ fragments are produced at the presynaptic terminal within late endosomes (Ye and Cai, 2014;Ye et al, 2017).…”
supporting
confidence: 76%
See 4 more Smart Citations
“…Ye and Cai (2014) recently reported that BACE1 accumulates in late endosomes that cluster at presynaptic terminals of hippocampal neurons in the human APP (hAPP) transgenic mouse model of AD, which produces amyloid pathology in mice comparable to human AD, and in AD patient brains. Given that the lumen of late endosomes is acidic, which is necessary for optimal BACE1 activity (Das et al, 2013), this finding is consistent with the hypothesis that A␤ fragments are produced at the presynaptic terminal within late endosomes (Ye and Cai, 2014;Ye et al, 2017).…”
supporting
confidence: 76%
“…As mentioned previously, postmortem AD patient brains also display accumulations of BACE1-containing late endosomes at presynaptic terminals; however, snapin levels are not altered in either hAPP mice or AD patients (Ye et al, 2017).…”
supporting
confidence: 55%
See 3 more Smart Citations